Reverse Gender Gap in Schooling in Bangladesh: Insights from Urban and Rural Households - Asadullah, Mohammad Niaz (2012)
This paper documents a reverse gender gap in secondary schooling outcomes in Bangladesh drawing upon several rounds of nationally representative household survey data. In terms of enrolment status and years of schooling completed, boys are found to lag behind girls in the rural as well as in the urban area. Within the urban sample, the gender gap is widest in the non-metropolitan area. These findings are robust to extensive control for demand and supply-side determinants of schooling and remain unchanged even when we use a within household estimator. We consider one hypothesis, namely gender-differentiated response to a conditional cash transfer program to reconcile the findings of this reverse gender gap.